Structure-activity relationships of nickel-hexaaluminates in reforming reactions part II: activity and stability of nanostructured nickel-hexaaluminate-based catalysts in the dry reforming of methane - Roussière, Thomas Luc; Schulz, Linus; Schelkle, Korwin; Wasserschaff, Guido; Milanov, Andrian; Schwab, Ekkehard; Deutschmann, Olaf; Jentys, Andreas; Lercher, Johannes; Schunk, Stephan A. (ChemCatChem, 2014)
Abstract Nihexaaluminates exhibiting a high magnetoplumbite or ??-alumina phase content (>80?wt?%) and high specific surface areas (10?30?m2?g?1) were investigated under dry reforming conditions. Ni content and choice of mirror plane cation are the key factors controlling the structure?property relationship in the dry reforming reaction of CH4. The Ni content is favorably kept below a threshold of y=0.25 in ANiyAl12-yO19?δ, (A=Ba, La, Sr) to ensure controlled nanoparticle formation and to avoid uncontrolled Ni0 nanoparticle growth apart from the support. Sr,Ni and Ba,Ni?hexaaluminates promote high activity of the catalyst in the dry reforming reaction of CH4, but show fast deactivation if the Ni content is maladjusted in the hexaaluminate framework (y≥0.5). La,Ni?magnetoplumbites display much lower activity accompanied by fast deactivation. The use of very high calcination temperatures (1600?°C) resulting in low specific surface area is detrimental to the activity in the dry reforming of CH4, simultaneously higher hexaaluminate phase content obtained undoes catalytic stability, reasoned by Ni0 nanoparticles produced after reduction cannot be stabilized over surface defects typically found on hexaaluminate platelets calcined at moderated temperatures (<1300?°C). As a result, larger metallic Ni ensembles are built up, selectivity to coke is increased and catalytic stability is compromised.
Gesehen am 03.09.2020